Relationship Between Comorbidity, Chronic Diseases, ICU Hospitalization, and Death Rate in the Elderly With Coronavirus Infection - Hamed Akhavizadegan; Mahmood Aghaziarati; Mohammad Ghasem Roshanfekr Balalemi; Zahra Arman Broujeni; Fatemeh Taghizadeh; Isa Akbarzadeh Arab; Majid Janani (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: The association of comorbidity diseases, such as diabetes and hypertension with the severity of Coronavirus Disease 2019 (COVID-19) has been repeatedly assessed. However, less research has specifically addressed the elderly. This study aimed to describe the demographic and clinical characteristics and evaluate the relationship between comorbidities, and the rates of Intensive Care Unit (ICU) hospitalization and death due to COVID-19 in the elderly. Methods & Materials: This retrospective study was conducted in elderly patients with COVID-19 admitted to Baharloo Hospital. Demographic information, types of underlying diseases, and need for hospitalization in the ICU or death in hospital among the hospitalized patients from March 2020 to July 2020 was extracted from the COVID-19 hospital database. The logistic regression model was used to estimate the Odds Ratio (OR), as a separate measure of the association between the research variables' outcomes (death & hospitalization outcomes in the ICU). Results: A total of 522 elderly patients were included in the study. Approximately 77% (n=422) of the elderly survived and 23% (n=100) died. The study participants' mean±SD age was 72.55±8.44 years. besides, and about 54%(n=281) were males. Logistic regression model results suggested that the odds of death in the study participants with ≥2 underlying diseases equaled 1.69 (OR=1.69, 95%CI: 0.97-2.91, P=0.04). Moreover, the odds of ICU hospitalization in them was 2.26 (OR=2.26, 95%CI: 1.34-3.81, P=0.002) time higher than their counterparts who did not have underlying diseases, i.e., statistically significant. Conclusion: Our results are expected to impact preventive interventions and take a more targeted approach to prioritize older patients with risk factors, rather than adopting calendar age policies as a general indicator for risk assessment.